Law Enforcement Of Criminal Offense On Labor Law As Protection To Labor Wages - Siciliya Mardian Yo'el; Huzaimah Al Anshori (Fakultas Hukum Universitas Mataram, 2019)
As the regulator, government protects workers’ rights to decent wages by regulating criminal sanctions against parties who violate the provisions regarding wages. This regulation can be found in Article 185 (1) in juncto Article 90 (1) Law Number 13 of 2003 concerning Labor which specifically regulates wages. The aim of this research is to describe law enforcement, article 185 (1) in juncto article 90 (1) and to analyze the effectiveness of article 185 (1) in juncto article 90 (1) in protecting workers’ rights of minimum wages. This research is using empirical legal research with a sociological juridical approach. This research is using primary data collected by field research, and secondary data obtained through library research. The results of the study show that in Kediri, the law enforcement for criminal offence in labor law, especially about wages is committed out by the Labor Inspector. However, labor inspection is still conducted by big and medium industries only, while for the small or micro enterprises sectors it is not found. Furthermore, Article 185 (1) in juncto Article 90 (1) it is considered effective protecting labor wages in a big and medium industrial only, because in the small or micro enterprises, there are many workers who get salary below the minimum wages